Illegal drugs and periodontal conditions. Issue 1 (2nd October 2022) - Quaranta, Alessandro; D'Isidoro, Orlando; Piattelli, Adriano; Hui, Wang Lai; Perrotti, Vittoria
Abstract: In recent years, the practice of dentistry and periodontology has become complicated by several risk factors, including the treatment of an increasing number of patients with substance use disorder. This review presents an update in the current literature of the impact of illegal drug use on periodontal conditions and their possible effect as risk factors or indicators. The main illegal drugs that may have an impact on periodontal health and conditions are described, including their effect, medical manifestations, risks, and the overall effect on oral health and on the periodontium. Where available, data from epidemiologic studies are analyzed and summarized. The clinical management of periodontal patients using illegal drugs is reported in a comprehensive approach inclusive of the detection of illicit drug users, screening, interviewing and counseling, the referral to treatment, and the dental and periodontal management. With regard to the impact of illegal substance use on periodontal conditions, there is moderate evidence that regular long‐term use of cannabis is a risk factor for periodontal disease, manifesting as a loss of periodontal attachment, deep pockets, recessions, and gingival enlargements. Limited evidence also shows that the use of cocaine can cause a series of gingival conditions that mostly presents as chemical induced‐traumatic lesions (application of cocaine on the gingiva) or necrotizing ulcerative lesions. There is a scarcity of data regarding the impact of other drug use on periodontal health. There is evidence to suggest that regular long‐term use of cannabis is a risk factor for periodontal disease and that the use of cocaine can cause a series of periodontal conditions. The dental treatment of subjects that use illegal substances is becoming more common in the daily clinical practice of periodontists and other dental clinicians. When the clinicians encounter such patients, it is essential to manage their addiction properly taking into consideration the impact of it on comprehensive dental treatment. Further studies and clinical observations are required to obtain sound and definitive information.